Fish Shop Menu 2020 - Shop, Fish (Technological University Dublin, 2020)
There is something blissful about a no-choice menu. Fish Shop became a set-menu operation after Peter Hogan and Jumoke Akintola opened a more casual bar around the corner, on Benburb Street. The menu is written in Sharpie on the metro tiles, and it's all exquisite. A plate of turbot, asparagus and Jenny McNally's Carolus potatoes was a true treat last month, making this my favourite Dublin restaurant north of the River Liffey. https://arrow.tudublin.ie/menus21c/1498/thumbnail.jpg